Fibrin glue and demineralized bone matrix effect on autologus cartilage graft in microtia reconstruction - Dini Widiarni Widodo; Jenny Bashiruddin; Helmi Helmi; Alida Harahap; Nurjati Chairani Siregar (Oto Rhino Laryngologica Indonesiana, 2015)
Background: Microtia reconstruction is a challenge for ENT Head and Neck surgeons. Varioussurgical techniques using autograft cartilage have been done to perform auricular reconstruction.Knowledge of cartilage graft concerning resorption process that affected the size, form, and aestheticsubunit of the ear is mandatory. Purpose: To evaluate the success of cartilage autograft by identifyingchondrocyte apoptosis, tissue degradation based on cell character, matrix homogeneity, fibrosis,proteoglycans, collagen and Transforming Growth Factor β (TGF β) expression in application of FibrinGlue (FG) and or Demineralized Bone Matrix (DBM) after 12 weeks in microtia reconstruction by Nagatatechnique. Methods: Quasi-experiments. FG and/or DBM were applied on the rest of the 12 ear cartilageframework which was implanted on mastoid area. Apoptosis was examined by TUNEL. Safranin Ostaining and modified Mankin’s score was used to evaluate cartilage degradation and TGF β expressionby ELISA. Results: FG or DBM on cartilage graft showed significant increase in chondrocyte viabilitycompare with control group (p=0.00). Minimal fibrosis, more homogeneous extracellular matrix, decreasedproteoglycan and minimal thickening of collagen, had significant differences compared with control orFG-DBM group. Structure differences occurred among cartilage graft after 12 week implantation whereasFG showed minimal fibrous tissue, normal cell character, proteoglycan, collagen, and tissue homogeneity(p< 0.05). Conclusion: FG is highly recommended to reduce degradation of cartilage graft in microtiareconstruction. DBM can be still used to maintain chondrocyte viability, proteoglycans, and collagen. Keywords: cartilage graft, fibrin glue, demineralized bone matrix, transforming growth factor β, Mankinscore.ABSTRAK Latar belakang: Rekonstruksi mikrotia merupakan tantangan bagi ahli bedah THT-KL. Berbagaiteknik operasi menggunakan rangka telinga dengan tandur kartilago autologus telah dilakukan untukrekonstruksi mikrotia. Pengetahuan mengenai tandur kartilago sangat diperlukan, mengingat tandurdapat mengalami resorpsi dengan berjalannya waktu, sehingga mempengaruhi ukuran, bentuk, dan detilestetik subunit daun telinga. Tujuan: Mengetahui viabilitas kondrosit, degradasi jaringan berdasarkanperubahan karakter kondrosit, fibrosis, homogenitas matriks, ekspresi proteoglikan dan kolagenserta ekspresi transforming growth factor β (TGF β ) dengan atau tanpa fibrin glue (FG) dan/ataudemineralized bone matrix (DBM) pada rekonstruksi mikrotia setelah 12 minggu penanduran. Metode:Quasi-eksperimen. FG dan/atau DBM digunakan pada sisa tandur autologus kartilago rangka telinga,dilanjutkan pemeriksaan apoptosis dengan TUNEL. Pewarnaan Safranin O untuk menilai degradasijaringan dengan skor modifikasi Mankin dan ekspresi TGF β dengan ELISA. Hasil: penambahan FGatau DBM pada tandur kartilago, viabilitas sel meningkat berbeda bermakna dengan tanpa perlakuanatau FG-DBM.(p=0.00), fibrosis minimal, matriks lebih homogen, penurunan proteoglikan dan penebalankolagen minimal berbeda bermakna dengan kelompok tanpa perlakuan dan campuran FG-DBM. Terjadiperbedaan struktur jaringan setelah 12 minggu, FG mempunyai nilai fibrosis yang terendah, karaktersel normal, proteoglikan, kolagen, dan homogenitas jaringan (p<0,05). Kesimpulan: Penggunaan FGsangat dianjurkan untuk mengurangi degradasi tandur kartilago autologus pada rekonstruksi mikrotia. Dalam keadaan tidak memungkinkan dapat digunakan DBM karena masih baik dalam mempertahankanviabilitas kondrosit, proteoglikan dan kolagen. Kata kunci: tandur kartilago, fibrin glue, demineralized bone matrix (DBM), transforming growth factorβ (TGF β), Mankin score.